Apakah Talak Raj’i Memutuskan Ikatan Pernikahan atau Tidak - Ningsih, Fitri; Musyahid, Achmad; Akmal, Andi Muhammad (Penerbit Yayasan Daarul Huda Kruengmane, 2025)
This study aims to examine whether talak raj’I, in Islamic law, terminates the marriage bond or not. Talak raj’I is a single or double divorce in which the husband has the right to reconcile during the iddah period. Talak, in Islam, is a means to terminate the marriage bond between husband and wife. However, not all divorces have the same impact. Talak raj’I is a type of divorce that gives the husband the right to reconcile his wife during the iddah period. This study will examine in more depth the consequences of talak raj’I, especially whether the divorce terminates the marriage bond or not, and how it has implications for marital status. This study uses a qualitative approach with a library research method. Data were collected from various sources such as classical fiqh books, contemporary fiqh books, and related laws and regulations, especially the Compilation of Islamic Law (KHI). Data analysis was carried out descriptively-qualitatively to understand the concept of talak raj’I and its implications for marriage bonds.